Causes of Neonatal Stroke: Ibn Thalaj’s (Died in 975 AD) Viewpoints - Asadi, Mohammad Hossein; Changizi-Ashtiyani, Saeed; Amini, Saeed (Iranian Journal of Child Neurology, 2025)
Although stroke has long been recognized as an adult health problem that causes significant morbidity and mortality, it is also an important cause of brain injury in infants and children. The present article deals with this issue from the perspective of medical history. Physicians have tried throughout history to diagnose and treat this disease. One of the physicians who first accurately described this disease was Ibn Thalaj, who died in 975 AD. The hypotheses that he has raised about the causes of neonatal stroke, along with his recommendations for prevention and treatment, are intriguing. Exploring these hypotheses highlights the ongoing human endeavor to comprehend and combat diseases.